Analysis of the Short – Term Financial Equilibrium for Romanian Companies - Borlea, Sorin Nicolae; Achim, Monica Violeta (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
In this paper we analyzed the short-term financial equilibrium of the Romanian companies by using some indicators based on net working capital and current ratio. Our sample is computed by 64 big non-financial companies which are listed at Bucharest Stock Exchange for the period 2003-2012 and activate in different sectors of activities. In subsidiary, another objective of our study consists in offering a database for the average values of net working capital and current ratio indicators in different sectors of activity, indicators that are very important for short-term equilibrium analysis for any Romanian companies.